Pengaruh Kualitas Produk, Promosi, Harga, dan Tempat Terhadap Keputusan Pembelian - Permadi, Bambang; Maulana, Maulana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The problem in this study is the lack of consumers or customers who buy at Caffe Pojok from year to year. This study aims to determine the effect of Product Quality, Promotion, Price, and Place on Purchasing Decisions and to determine the effect of Product Quality, Promotion, Price, and Place simultaneously or together on purchasing decisions at Caffe Pojok. The research method used is a quantitative method. The data source used is primary data, obtained from distributing questionnaires to respondents. The technique used in determining the sample is accidental sampling. The data is processed and analyzed using multiple linear regression and using SPSS for Windows Version 26. The results of this study indicate that (1) The effect of the coefficient of determination (R Square) is 0.140 or equal to 14.0%. This figure means that product quality, promotion, price, and place have an effect on purchasing decisions by 14.0%. (2) The influence of independent variables simultaneously on the dependent variable obtained a calculated f value of 3.881 and an f table of 2.460 or 3.881 > 2.460 with a significant probability value of 0.012 or 0.000 < 0.05 (H0 is rejected and H1 is accepted). So it can be said that there is a significant influence simultaneously between the independent variables on the dependent variable and can be used to predict the influence on purchasing decisions.